MENULIS TEKS DESKRIPSI DENGAN PEMANFAATAN MEDIA LINGKUNGAN SEBAGAI SUMBER BELAJAR - Devi Tirta Sari; Salam Salam (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Writing Descriptive Text using Environmental Media as a Learning Source. This study aims to describe the ability to write descriptive text of seventh grade students of SMP Negeri 2 Labakkang Pangkep by utilizing environmental media as a learning resource. This type of research is quantitative research. The population in this study were all grade VII students at SMPN 2 Labakkang, Pangkep Regency, totaling 180 students. Sampling was done by using simple random sampling technique. The selected sample, that is class VII R.A. Kartini. The instrument used in this study was a written test. The data analysis technique used quantitative descriptive. The results showed that the level of ability to write descriptive text of the seventh grade students of SMP Negeri 2 Labakkang using environmental media as a learning resource was in the quite capable category.